The Effect of Consuming Eggs and Iron Tablets on Increasing Hb Levels in Adolescent Girls at the Aisyiyah Orphanage in Klaten - Kuswati Kuswati; Siti Yulaikah (Placentum)
Background: Anemia is a common problem among teenagers. Anemia control in adolescent girls and women of childbearing age (WUS) by providing Fe tablets..Eggs are one of the foods that contain iron and can be a substitute for Fe tablets.